Perceptions of the local beekeepers on the diversity and flowering phenology of the melliferous flora in the community of Xmabén, Hopelchén, Campeche, Mexico - Milca E. Coh-Martínez; William Cetzal-Ix; Jesús F. Martínez-Puc; Saikat Kumar Basu; Eliana Noguera-Savelli; Manuel J. Cuevas (BMC, 2019)
Abstract Background The knowledge of native melliferous flora (MF) may contribute to identify the diversity of species available for beekeeping activities during the dry and rainy seasons of the year in the Yucatan Peninsula (YP) region. The acute shortage of food resources considerably reduce local honey production and needs to be addressed appropriately. The objective of this study has been identifying the local MF, their nectar and pollen contribution, their flowering patterns, and the criteria of the vegetation to be established adjacent to local apiaries for stable production of quality honey. The study also investigates how this approach helps to complete the annual flowering cycle required to maintain the honeybee colonies, thereby preventing swarm escapes during periods of acute food stress in the community of Xmabén, Hopelchén, Campeche, Mexico. Methodology We conducted a comprehensive survey based on interviews with 40 local beekeepers and a review of herbarium specimens (CICY) of the database of the global information network on the native MF biodiversity with high apiculture potential, the contribution of nectar and pollen they provide, and their flowering patterns. Furthermore, we documented interviews with the same beekeepers on the necessary conditions for establishing the ideal components of vegetation in areas adjacent to apiaries for high-quality honey production in the Xmabén community of Hopelchén, Campeche, Mexico. Results We have identified 56 native MF species with apiculture potential, that need to be planted around the apiaries for assisting honeybees in successfully running the beekeeping production cycle. Hence, the MF diversity of Xmabén community constitutes a valuable resource for successful beekeeping in the region and adjoining localities. We found that 22.5% of local beekeepers are dedicated exclusively to apilcilture, while 77.5% practice it as a secondary activity due to better sources of income in agriculture (60%), masonry (10%), and livestock management (7.5%). The data generated can help in further expansion of the local apiaries, beekeeping business, and in building future opportunities for the local apiculture industry. Indigenous knowledge of the beekeepers was comprehensive and corroborated the technical information on MF collected from the herbarium, further emphasizing the value of indigenous knowledge on traditional beekeeping practices. Conclusion From the perspective of human ecology, our study reveals the need of collecting, analyzing, and interpreting indigenous knowledge to facilitate traditional beekeeping practices of the region without using expensive, modern technology to solve ecosystem-based problems through long-term, sustainable, traditional, and environment friendly approaches.